Pengaruh Konflik Kerja-Keluarga, Pengetahuan Kewirausahaan, dan Literasi Digital Terhadap Niat Melanjutkan Usaha pada Perempuan di DKI Jakarta - Nadhifah Azzura; Terrylina Arvinta Monoarfa; Bagus Kharismawan (Indo Publishing, 2026)
Women entrepreneurs in urban areas such as DKI Jakarta face various challenges in maintaining the sustainability of their businesses, particularly regarding role conflicts between work and family as well as the demands of adapting to developments in digital technology. This study aims to analyze the influence of work-family conflict, entrepreneurial knowledge, and digital literacy on the intention to continue business among women entrepreneurs in DKI Jakarta. This study employs a quantitative approach using a survey method. Data were collected via a questionnaire administered to 100 respondents selected using purposive sampling. The units of analysis in this study are female entrepreneurs residing in DKI Jakarta who have been running a business for at least 6 months and live with their families. The data were analyzed using simple linear regression. The results indicate that work-family conflict does not significantly influence the intention to continue the business. Meanwhile, entrepreneurial knowledge and digital literacy have a positive and significant effect on the intention to continue a business. These findings indicate that individual knowledge and skills play a more dominant role in promoting business sustainability than role conflict. This study is expected to serve as a reference for improving entrepreneurial competencies and digital literacy, as well as for educational institutions to provide support aimed at sustaining women’s businesses amid the dynamics of the business environment.